2006
DOI: 10.1128/jb.188.7.2715-2720.2006
|View full text |Cite
|
Sign up to set email alerts
|

Liberation of Zinc-Containing L31 (RpmE) from Ribosomes by Its Paralogous Gene Product, YtiA, inBacillus subtilis

Abstract: We have found that alternative localization of two types of L31 ribosomal protein, RpmE and YtiA, is controlled by the intracellular concentration of zinc in Bacillus subtilis. The detailed mechanisms for the alternation of L31 proteins under zinc-deficient conditions were previously unknown. To obtain further information about this regulatory mechanism, we have studied the stability of RpmE in vivo and the binding affinity of these proteins to ribosomes in vitro, and we have found that liberation of RpmE from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 21 publications
6
96
0
Order By: Relevance
“…62) Further in vivo and in vitro studies indicated that (i) RpmE is de-stabilized by overexpression of ytiA, (ii) YtiA is incorporated into the ribosome more efficiently than RpmE, and (iii) YtiA can be incorporated into at least a portion of the ribosomes that contain RpmE and incorporation of YtiA results in the liberation of RpmE. 67) From these results, a model for the switching between the two types of L31 was proposed (Fig. 2).…”
Section: Mechanisms Of Switching Between the Two Types Of L31 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…62) Further in vivo and in vitro studies indicated that (i) RpmE is de-stabilized by overexpression of ytiA, (ii) YtiA is incorporated into the ribosome more efficiently than RpmE, and (iii) YtiA can be incorporated into at least a portion of the ribosomes that contain RpmE and incorporation of YtiA results in the liberation of RpmE. 67) From these results, a model for the switching between the two types of L31 was proposed (Fig. 2).…”
Section: Mechanisms Of Switching Between the Two Types Of L31 Proteinmentioning
confidence: 99%
“…2). 60,62,67) During exponential growth in CSM, which is considered to constitute zinc-sufficient conditions, RpmE contains a zinc ion bound to the CxxC motif and thus is stable. In addition, active Zur protein binds to a motif in the promoter of ytiA, the so-called ''Zur box,'' which is highly conserved among the genes regulated by Zur, 65) and thus represses the expression of ytiA.…”
Section: Mechanisms Of Switching Between the Two Types Of L31 Proteinmentioning
confidence: 99%
“…Panina et al (2003) do not explain how CϪ forms replace Cϩ forms in ribosomes. We have recently found that when YtiA is added to RpmE-containing ribosome fractions, YtiA-containing ribosomes are detected, suggesting that the affinity of YtiA to ribosomes is higher than that of RpmE and thus newly synthesized YtiA can liberate RpmE from ribosomes (Akanuma et al, 2006). Zinc is an essential trace metal ion for all living cells, which is required for catalytic activity of enzymes and also for structural folding in protein-protein and protein-DNA interactions (Berg and Shi, 1996).…”
Section: Duplication Of R-protein Genes and The Zinc Homeostasismentioning
confidence: 99%
“…8b). The low occupancy of L31 can be explained by its flexible binding mode, which may also be important for the function of L31 as a Zn 21 reservoir for the cell 28 .…”
mentioning
confidence: 99%